2011
DOI: 10.3858/emm.2011.43.11.071
|View full text |Cite
|
Sign up to set email alerts
|

Higher infiltration by Th17 cells compared with regulatory T cells is associated with severe acute T-cell-mediated graft rejection

Abstract: The aim of this study was to evaluate whether the Th17 and Treg cell infiltration into allograft tissue is associated with the severity of allograft dysfunction and tissue injury in acute T cell-mediated rejection (ATCMR). Seventy-one allograft tissues with biopsy-proven ATCMR were included. The biopsy specimens were immunostained for FOXP3 and IL-17. The allograft function was assessed at biopsy by measuring serum creatinine (Scr) concentration, and by applying the modified diet in renal disease (MDRD) formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 39 publications
4
32
0
Order By: Relevance
“…In normal individuals, Tregs can modulate auto-immune effector T cell function through suppressive cytokines IL-10, IL-35 and TGFβ (27, 33, 34). This system of Treg-Th17 balance may be deficient in individuals who are undergoing chronic rejection of heart or lung allografts as has been reported in kidney allograft models (35). …”
Section: Introductionmentioning
confidence: 81%
“…In normal individuals, Tregs can modulate auto-immune effector T cell function through suppressive cytokines IL-10, IL-35 and TGFβ (27, 33, 34). This system of Treg-Th17 balance may be deficient in individuals who are undergoing chronic rejection of heart or lung allografts as has been reported in kidney allograft models (35). …”
Section: Introductionmentioning
confidence: 81%
“…In kidney transplantation, Th17 cell infiltration hastens chronic rejection and fibrosis in allograft tissue by promoting lymphoid neogenesis [31]. In our previous report, we demonstrated that higher levels of infiltration of Th17 cells in renal allograft tissue are associated with more severe inflammation and chronic changes in the allograft tissue, and were significantly associated with the progression of interstitial fibrosis and tubular atrophy [32].…”
Section: Discussionmentioning
confidence: 96%
“…[3][4][5] Additionally, CNIs induce undesirable changes in the immune response after kidney transplantation, including a reduction in the proportion and function of CD4 + regulatory T cells (CD4 + Treg cells) within the peripheral blood mononuclear cell (PBMC) population, [6][7][8] and an up-regulation of T helper type 17 (Th17) cell-associated pathways, which are involved in allograft rejection. [9][10][11][12][13][14][15][16][17] Hence, CNI-based immunosuppression may in fact contribute to the progression of chronic allograft dysfunction in kidney transplant recipients (KTRs).…”
Section: Introductionmentioning
confidence: 99%